Evidence-based reproductive health care in Cameroon: population-based study of awareness, use and barriers - Alan TN Tita; Beatrice J Selwyn; D Kim Waller; Asha S Kapadia; Sylvestre Dongmo (The World Health Organization, 2005)
OBJECTIVE: To estimate the prevalence of awareness and use of evidence-based reproductive health interventions and to describe the barriers associated with the use of evidence-based interventions among health providers in north-west Cameroon. METHODS: In February 2004, a population-based descriptive study of the awareness and use of 13 evidence-based interventions targeted health workers providing reproductive health care. Their awareness and use of a composite of four vital interventions was also evaluated. These were peripartum use of antiretrovirals to prevent transmission of HIV, antenatal corticosteroid administration, magnesium sulfate prophylaxis and active management of placental delivery with uterotonics. In-depth interviews with key informants were conducted as part of a qualitative substudy to discover the barriers to the use of evidence-based interventions. FINDINGS: Overall, 91.4% (328/359) of reproductive health workers were surveyed. Their awareness of evidence-based interventions varied from 29% for the use of antenatal corticosteroids to 97% for the use of iron and folic acid supplementation during pregnancy. Their use of these interventions ranged from 10.2% for antenatal corticosteroids to 94.8% for iron and folic acid supplementation. Only 50/322 (15.5%; 95% confidence interval (CI) = 11.8-20.0) of health workers were aware of all four vital interventions, and only 12/312 (3.8%; 95% CI = 2.0- 6.6) reported using all of them regularly. A total of 26 key informants participated in the qualitative substudy. A deficiency in the education and training of health workers, especially a lack of continuing education, was commonly identified as the most important barrier to their awareness of evidence-based practices. A lack of awareness and a lack of supplies and materials were the main barriers to practice. CONCLUSION: The awareness and practice of important evidence-based reproductive health interventions were less than optimal. To improve maternal and perinatal outcomes both remedial programmes to enhance awareness, including continuing education for health workers, and the provision of necessary supplies are needed.